A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae) - Gil-Santana, Hélcio R.; Ferreira, Rodrigo Lopes (Zootaxa, 2016)
Dohrnemesa oliveirai sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Emesini) is described from state of Pará, Brazil, based on a male specimen. The male genitalia of D. carvalhoi (Wygodzinsky, 1966) is described for the first time and some notes about D. albuquerquei (Wygodzinsky, 1966) are furnished.